Solve equations using De Moivre's theorem:
1. x^7 + x^4 + x^3 + 1 = 0
2. x^7 - x^4 + x^3 - 1 = 0
I tried multiplying with (x - 1). Also tried putting x^3 = y; didn't work.
Ok, This one is sort of a trick question in a way because the answer requires you to notice something not totally obvious.
It took a bit of toying with this to see what they are after.
Take
x^7 + x^4 + x^3 + 1 = x^4(x^3 + 1) + (x^3 + 1) = (x^4 + 1)(x^3 + 1) = 0
I took the 2 leftmost terms of the sum and factored those separately and a factor just happens to be the same as the remaining terms in the sum so it can all be expressed by the product of those two terms above. Clearly the problem was set up this way.
Now in order for the product to be zero one or the other or both of those two factors must be 0, i.e.
(x^4 + 1) = 0 or (x^3 + 1) = 0, or both
This is where D'Moivre's theorem comes into play as you use it to immediately pick out the roots of each of these two terms.
(x^4 + 1) = 0, e^(i 4 theta) = e^(i (2k+1) pi) k an integer (do you understand why? because -1 = e^(i (2k+1) pi) )
theta = (2k+1) pi/4 for k=0,1,2,3 they just repeat after k=3
similarly
(x^3 + 1) = 0, e^(i 3 theta) = e^(i (2k+1) pi)
theta = (2k+1) pi/3 for k=0,1,2
take e^(i theta) for each of those theta's above and those are your 7 roots of the original polynomial.
You give the 2nd one a shot now that you've got an outline of how to proceed.